THE INFLUENCE OF OCCUPATIONAL SAFETY AND HEALTH ON EMPLOYEE PERFORMANCE AT PT MAKASSAR MEGA PRIMA - M.Irwan Suaeb; Moh Arga Wijana (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
This research aims to find out whether occupational safety and health influence employee performance at PT Makassar Mega Prima. Data collection uses primary data obtained from questionnaires using the simple random sampling method. The population was all permanent employees in the production department at PT Makassar Mega Prima, totaling 72 people, while the sample taken was 61 respondents. The results of the questionnaire have been tested for validity and reliability, and classical assumptions in the form of normality assumptions and heteroscedasticity assumptions have also been tested. The analysis method uses multiple regression analysis. The research results show that occupational safety partially does not influence employee performance, while occupational health partially influences employee performance.